(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
Teachers are an important source of inspiration for their students. Although educational research considers inspiration to be an important motivational construct that generates positive results for students, the different conceptual interpretations of the construct have made its study difficult. This situation is accentuated in the context of Latin America, due to the scarcity of empirical studies that contribute to its understanding. Considering the teacher as a source of inspiration and based on the inspiration model of Thrash & Elliot (2003, 2004), this study seeks to understand how students experience inspiration. Twenty university students were interviewed about their experiences of inspiration about their professors. The interviews were evaluated through thematic analysis. The results revealed 5 themes that highlight the characteristics of the inspiring teacher. Additionally, the thematic analyzes verified the existence of the three characteristics of the inspiration model (evocation: 1 theme, transcendence: 3 themes, and motivation: 4 themes). The study contributes by laying the foundations for formulating a guide that characterizes the inspiring teacher. As well as formulate positive insights focused on the characteristics of inspiration that allow students to transcend professionally through their university studies.